Conversion of Green Silica from Corn Leaf into Zeolites Na A-X - Teguh Kurniawan; Dhimas Satria; Juniafit Bima Saputra; Muhammad Roil Bilad; Nik Abdul Hadi Md Nordin; Hairus Abdullah (Indonesian Journal of Science and Technology, 2022)
Combustion of corn leaf as a model of biomass from agricultural waste is a simple way to obtain the energy. It produces a low-value by-product of ash and is rich in silica that can become a precursor for zeolite production. In this study, acid-treated corn leaves combustion was performed to produce high purity silica (SiO2). The diffraction pattern suggested that the extracted silica was amorphous without the impurities phase. Additionally, the nitrogen isotherm indicated that the material was highly mesoporous silica with a total surface area of 200 m2/g. The hydrothermal method was then applied with a composition molar ratio of 1.25SiO2:1Al2O3:5Na2O:250H2O to synthesize zeolites from the silica. The temperature and time effect on the hydrothermal zeolite’s synthesis was investigated. The diffraction pattern shows that high crystalline zeolite Na A-X was produced at temperatures of 100°C and 8 h hydrothermal time. According to nitrogen physisorption analysis, the zeolite Na A-X consisted of micropores with a total surface area of 270 m2/g. The morphology of zeolite Na A-X was cube for the Na-A and octahedral for the Na-X. The hydrothermal temperature and time highly affected the zeolite formed. This research suggested that the ash waste could be valorized through conversion into a high economic value zeolites.